Human recombinant alkaline phosphatase inhibits ex vivo platelet activation in humans - Tunjungputri, Rahajeng N.; Peters, Esther; van der Ven, Andre; de Groot, Philip G.; de Mast, Quirijn; Pickkers, Peter (Thrombosis and Haemostasis, 2016)
Sepsis-associated acute kidney injury (AKI) is associated with high morbidity and mortality. Excessive platelet activation contributes to AKI through the formation of microthrombi and amplification of systemic inflammation. Two phase II trials demonstrated that bovine-intestinal alkaline phosphatase (AP) improved renal function in critically ill patients with sepsis-associated AKI. In this study, we characterised the platelet-inhibiting effects of a human recombinant AP. Whole blood and platelet-rich plasma (PRP) of healthy volunteers (n=6) was pre-treated ex vivo with recAP, whereafter platelet reactivity to ADP, collagen-related peptide (CRP-XL) and Pam3CSK4 was determined by flow cytometry. RecAP (40 U/ml) reduced the platelet reactivity to ADP (inhibition with a median of 47%, interquartile range 43–49%; p<0.001) and tended to reduce platelet reactivity to CRP-XL (9%, 2–25%; p=0.08) in whole blood. The platelet-inhibiting effects of recAP were more pronounced in PRP both for ADP- (64%, 54–68%; p=0.002) and CRP-XL-stimulated samples (60%, 46–71%; p=0.002). RecAP rapidly converted ADP into adenosine, whereas antagonism of the A2A adenosine receptor partially reversed the platelet inhibitory effects of recAP. Platelets of septic shock patients (n=5) showed a 31% (22–34%; p=0.03) more pronounced reactivity compared to healthy volunteers, and this was completely reversed by recAP treatment. In conclusion, we demonstrate that recAP inhibits ex vivo human platelet activation through dephosphorylation of ADP and formation of adenosine as its turnover product. RecAP is able to reverse the platelet hyperreactivity present in septic shock patients. These effects may contribute to the beneficial effects of recAP as a new therapeutic candidate for sepsis-associated AKI.
Keywords: Platelet activation; antiplatelet agents; sepsis; acute kidney injury; alkaline phosphatase